Conspecific and heterospecific plant densities at small-scale can drive plant-pollinator interactions - Janovský, Zdeněk; Mikát, Michael; Hadrava, Jiří; Horčičková, Eva; Kmecová, Kateřina; Požárová, Doubravka; Smyčka, Jan; Herben, Tomáš (PloS one, 2013)
Generalist pollinators are important in many habitats, but little research has been done on small-scale spatial variation in interactions between them and the plants that they visit. Here, using a spatially explicit approach, we examined whether multiple species of flowering plants occurring within a single meadow showed spatial structure in their generalist pollinator assemblages. We report the results for eight plant species for which at least 200 individual visits were recorded. We found that for all of these species, the proportions of their general pollinator assemblages accounted for by particular functional groups showed spatial heterogeneity at the scale of tens of metres. This heterogeneity was connected either with no or only subtle changes of vegetation and flowering species composition. In five of these species, differences in conspecific plant density influenced the pollinator communities (with greater dominance of main pollinators at low-conspecific plant densities). The density of heterospecific plant individuals influenced the pollinator spectrum in one case. Our results indicate that the picture of plant-pollinator interactions provided by averaging data within large plots may be misleading and that within-site spatial heterogeneity should be accounted for in terms of sampling effort allocation and analysis. Moreover, spatially structured plant-pollinator interactions may have important ecological and evolutionary consequences, especially for plant population biology.
Keywords: distribuce rostlin; Pollination; Population Density; Magnoliopsida; Plant Dispersal; Ecosystem; Biological Evolution; hustota populace; Butterflies; symbióza; zvířata; včely; Coleoptera; Symbiosis; Bees; Diptera; Pollen; biologická evoluce; Flowers; brouci; květy; pyl; Animals; motýli; opylení; ekosystém